Spatial and morphologic features of lenses with different axial lengths in cataract patients: a swept-source optical coherence tomography-based study - Chao Chen; Jiaqi Meng; Kaiwen Cheng; Ching Kang; Liguang Zhou; Haike Guo; Xiangjia Zhu (BMC Ophthalmology, 2024)
Abstract Background To investigate the spatial and morphologic features of lenses with different axial length (ALs) in cataract patients using swept-source optical coherence tomography (SS-OCT). Methods Totally 105 eyes of 105 patients scheduled to have cataract surgery were included. Eyes were divided into the control (AL < 24.5 mm), moderate myopia (MM, 24.5 ≤ AL < 26 mm) and high myopia (HM, AL ≥ 26 mm) groups. Spatial features including lens vault (LV) and iris-to-lens distance (ILD), and morphologic features including radii of curvature of anterior and posterior surface (Ra, Rp), lens diameter (LD) and lens thickness (LT) were measured in eight directions by SS-OCT. Results Spatially, the HM group had larger LV and ILD than the control group (both P < .05). LV and ILD were negatively correlated with AL, respectively (LV: r = -.484, P < .0001; ILD: r = -.656, P < .0001). Morphologically, both MM and HM groups had greater Ra and Rp than the control group. Ra was positively correlated with AL (r = .622, P < .0001), while the relationship between Rp and AL was non-linear. Moreover, the MM and HM groups had larger LD than the control group (both P < .001). Anterior LT was thinner in the HM than in the MM group (P = .026), while posterior LT between these two groups was similar. When compared in eight directions, similar trends were seen in Ra, Rp and LD, and the HM group showed a greater difference in Ra between horizontal and vertical directions. Conclusions This SS-OCT-based study showed that longer axial length is associated with a flatter lens, which was mainly attributed to the increase of Ra and LD. Longitudinal studies would be necessary to establish a causal relationship and temporal progression.